Tunisia : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency, Banking Supervision, Securities Regulation, Insurance Regulation, and Payment Systems. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper presents findings of the Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on Monetary and Financial Policy Transparency, Banking Supervision, Securities Regulation, Insurance Regulation, and Payment Systems for Tunisia. Over the past decade, the financial system has been extensively modernized. Significant progress has also been achieved toward placing the banking system on a sound footing. The analysis shows that, despite the large exposure to credit risk, the banking system appears unlikely to suffer from a generalized crisis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet